Stability of Iceland type berm breakwaters - Sveinbjornsson, P.I. (author) (TU Delft, Civil Engineering and Geosciences, Hydraulic Engineering, 2008)
A major part of the breakwaters constructed in the world are the so-called conventional rouble mound breakwaters, which consist of a core, a filter layer and a heavy armour layer. An alternative to the conventional rouble mound breakwater is a berm breakwater. Berm breakwaters have mainly developed in two directions over the last couple of decades. On the one hand a dynamically stable structure, where reshaping is allowed. And on the other hand a more stable multi layered structure often referred to as Icelandic type berm breakwater. When there is a rock quarry, relatively close to the construction site, which is dedicated to the breakwater project, the Icelandic type has proven to be very attractive economically. The basic reason for that is that unlike the other types the Icelandic type utilizes the quarry 100%. This M.Sc. thesis focuses on the Icelandic type berm breakwater. Before an Icelandic type berm breakwater is constructed the stones are divided into classes depending on their size. The smaller armour stones are then placed rather deep where the influence of the wave attack is less, as well as on the rear end of the structure, while the largest stones are placed where the largest wave attack is expected. The goals of the project are the following: a) Design rules for the transaction of stone classes with depth have not yet evolved and the main goal of this project was to develop a stability criterion for the stones in that area (Primary goal). b) Stones on berm. Since the total amount of the largest stones (Class I) is usually limited, the combination of the amount of large stones on the berm and down the berm is important (Secondary goal). c) Recession. Recession will be measured in each test and thereby a large database on the subject will be made available for further research on the subject (Secondary goal). d) The location of the transition of the original and the reshaped profiles as the berm height changes as well as for different stone setups. This is also closely related to the primary goal of ...